Post-mortem computed tomography (PMCT) and PMCT-angiography after cardiac surgery. Possibilities and limits - Vogel, Beatrice; Heinemann, Axel; Tzikas, Antonios; Poodendaen, Chanasom; Gulbins, Helmut; Reichenspurner, Hermann; Vogel, Hermann; Püschel, Klaus (Archiwum Medycyny Sądowej i Kryminologii/Archives of Forensic Medicine and Criminology, 2013)
Background: PMCT is a well-known tool of the forensic pathologist. It is employed worldwide. PMCT-angiography offers additional insights. This paper intends to demonstrate possibilities of both methods after cardiac surgery. Material and Methods: Exemplary cases with typical findings were selected from our own collection. PMCT was performed as whole body CT (1mm slice, pitch 1.5, 130kV, 180-130mAs, 16 slice MDCT). In PMCT-angiography, contrast material (1.2 litres) is injected into the arteries (arterial phase, also documented with a whole body CT). Thereafter, contrast material is injected into the veins (venous phase, also documented with a whole body CT). The final CT is obtained after circulation has been provoked with a special pump (circulatory phase). Results: PMCT visualised pseudoarthrosis and fractures of the sternum, implanted valves (TAVI) encroaching the ostia of the coronary arteries, bleeding and pericardial tamponade. PMCT-angiography showed the sources of the bleeding, vascular stenosis and obstruction and modified vascular supply. With respect to the postoperative care, malposition of tubes, drainages and complication of punctures could be seen. Conclusion: PMCT and PMCT-angiography can visualise complications and the cause of death. Such knowledge may allow for prevention of suffering and death. It may also aid in improving valve design and implantation procedures.